Neuroprotective effect against amyloidogenic transthyretin aggregates - Induced cytotoxicity on human neuroblastoma cell by phenolic-rich Centella asiatica extract - Fredrick Nwude Eze; Apinna Bunyapongpan; Porntip Prapunpoj (Heliyon)
Transthyretin (ATTR) amyloidosis is a progressive and life-threatening neurodegenerative disease caused by aggregation of the plasma transport protein, transthyretin, for which treatment is rare and cure unavailable. Centella asiatica is a small edible herb with a long history of neurological application in ethnomedicine. This work investigated whether hydrophilic extract of C. asiatica (CAB) could suppress the toxic effects of transthyretin amyloid aggregate (TTRa) in cell model derived from the same in vivo target. TTRa was prepared via thermal-induced aggregation. Chemical cross-linking and Tricine-SDS-PAGE, Thioflavin-T fluorescence, and TEM analyses confirmed that TTRa matched the profile of TTRL55P nonfibrillar amyloid aggregates. PrestoBlue cell viability assay revealed that exposure of IMR-32 human neuroblastoma cells to TTRa (2–8 μM) resulted in significant cytotoxicity. Conversely, exposure of IMR-32 cells to CAB did not adversely affect their viability. In addition, when IMR-32 cells were co-treated with TTRa and varied concentrations of CAB, the toxic effect of TTRa was significantly (p < 0.01) inhibited dose-dependently. The extract was found to possess potent radical scavenging effects, and quantitative RP-HPLC analysis showed that asiaticoside and phenolics were its main components. The cytoprotective effect against TTRa, antioxidant property, and good safety profile collectively suggest that CAB could be applied in the development of nutraceuticals or therapeutics against transthyretin amyloidosis.